Developing the ethics of implementation research in health. (December 2016) - Gopichandran, Vijayaprasad; Luyckx, Valerie; Biller-Andorno, Nikola; Fairchild, Amy; Singh, Jerome; Tran, Nhan; Saxena, Abha; Launois, Pascal; Reis, Andreas; Maher, Dermot; Vahedi, Mahnaz
Abstract Implementation research (IR) is growing in recognition as an important generator of practical knowledge that can be translated into health policy. With its aim to answer questions about how to improve access to interventions that have been shown to work but have not reached many of the people who could benefit from them, IR involves a range of particular ethical considerations that have not yet been comprehensively covered in international guidelines on health research ethics. The fundamental ethical principles governing clinical research apply equally in IR, but the application of these principles may differ depending on the IR question, context, and the nature of the proposed intervention. IR questions cover a broad range of topics that focus on improving health system functioning and improving equitable and just access to effective health care interventions. As such, IR designs are flexible and often innovative, and ethical principles cannot simply be extrapolated from their applications in clinical research. Meaningful engagement with all stakeholders including communities and research participants is a fundamental ethical requirement that cuts across all study phases of IR and links most ethical concerns. Careful modification of the informed consent process may be required in IR to permit study of a needed intervention. The risks associated with IR may be difficult to anticipate and may be very context-specific. The benefits of IR may not accrue to the same groups who participate in the research, therefore justifying the risks versus benefits of IR may be ethically challenging. The expectation that knowledge generated through IR should be rapidly translated into health policy and practice necessitates up-front commitments from decision-makers to sustainability and scalability of effective interventions. Greater awareness of the particular ethical implications of the features of IR is urgently needed to facilitate optimal ethical conduct of IR and uniform ethical review.